Some Characteristics of the Clottable Protein of Limulus Polyphemus Blood Cells - Solum, N. O (Thrombosis and Haemostasis, 1970)
1. The endotoxin-clottable protein of Limulus blood cell extracts has been studied. The concept of the clottable protein as a true cell protein was confirmed.2. 35–55% of total extractable protein was removed from the extracts by clotting. Polyacrylamide disc electrophoresis of the extracts showed 6 to 9 protein bands one of which was reduced in intensity by the clotting. Dimethylf ormamide could be used for fractionated precipitation of the proteins.3. The gel protein was easily soluble in HCl or NaOH and reprecipitated by neutralization. It was also soluble in 0.05 M formate/6.7 M urea pH 4.3 but not in neutral solutions of urea.4. Light absorption spectra of the gel protein in 0.188 N NaOH showed maxima at 283 mμ and 290 mμ, whereas one maximum, at 276 mμ, was observed in 0.189 N HCl. E1 %1 cm in 0.188 N NaOH was 10.4 and 11.1 at 283 mμ and 290 mμ, respectively, and 9.0 at 276 mμ in 0.189 N HCl.5. Data on the total amino acid composition of the gel protein are given. A mean minimal molecular weight of about 20,000 is calculated from these.6. In starch gel electrophoresis with a discontinuous acid buffer system the gel protein separated into two main zones. Possible relationships between these are discussed in terms of clotting mechanism.7. The data show that Limulus clottable protein differs markedly in its molecular characteristics from those of mammalian fibrinogens.